The Social Interaction Between Indigenous and Non-Indigenous Community in Malaysia - Sukhaimia, Nola Aprilia; Sinurat, Susilawati (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This study aims to collect, process, analyze and describe social interactions between indigenous and non-indigenous communities in Malaysia. This research is a descriptive study using qualitative data. Data collected using techniques, interviews, and documentation. Data analysis in the study was carried out using data reduction techniques, data interpretation and reduction of conclusions. The results showed that the Malay or indigenous community consisting of native Malaysians and Islamic and non-indigenous majority consisted of Chinese, Indians, Arabs and Thais, where they interacted with indigenous and non-indigenous populations who had an influence on the growth of life the community. The form of interaction varies based on motivation and interaction. 1) Interaction is carried out for business transactions, becausemany tourists go to Malaysia as a consumer and businessman as a means of the necessary facilities.2) Interaction activities when indigenous and non-indigenous communities meet at work, tourist attractions, schools, hospitals, highways. The meeting was like in school with motivation for friendship, finance, and romance. 3) Interactions that occur when both parties explore informationsuch as culture, language, and personal data. Interaction is more common when both parties go to a place and make a meeting. Interaction can be distinguished between indigenous and non-indigenous communities from language and physical form differences. The impacts of these changes are relationships, social, cultural, and linguistic.